Analisis Keaktifan Siswa Melalui Computer Based Instruction Model Simulasi dalam Pembelajaran IPA di MI 01 Rejang Lebong - Fitria, Zahratul; Prastowo, Andi (AR-RIAYAH: Jurnal Pendidikan Dasar, 2021)
Natural Science Learning (IPA) which is often considered difficult in the learning process takes place, It aims to reveal the application of Natural Science (IPA) learning using Computer Based Instructions to improve the activeness of learning sisswa. In this case Madrasah Ibtidaiyah 01 Rejang Lebong, one educator as the subject, data pumping techniques with Interviews, Documentation and observation as data analyst techniques. The result of this study is an analysis of Natural Science learning (IPA) using Computer Based Instruction simulation model in Madrasah Ibtidaiyah 01 Rejang Lebong there is an increase in learning outcomes and processes in teaching and learning can increase the activeness of learners in interacting both ways.